P0137FIRST RUSSIAN BOSIMILAR OF ECULIZUMAB IN THE TREATMENT OF AN ADULT PATIENT WITH ATYPICAL HEMOLYTIC UREMIC SYNDROME. (6th June 2020) - Lavrishcheva, Yulia; Jakovenko, Alexander; Kudlay, Dmitriy
Abstract: Background and Aims: The disease diagnostics results and the efficacy of pathogenetic treatment when transferring from the original drug to the biosimilar were evaluated during clinical observation of an adult patient with aHUS. Method: A 46-year-old patient has a history of hypertension since 2012 and maximum ABP of 230/130 mmHg. In 2016, newly diagnosed azotemia was identified (blood creatinine — 140 μmol/L, GFR by EPI — 54 mL/min/1.73m2). In 2018, the patient suffered an acute cerebrovascular accident in the vertebrobasilar area. On admission to Almazov National Medical Research Centre, blood test showed: creatinine – 260 μmol/L (GFR by EPI — 28 mL/min/1.73m 2 ), urea – 11.52 mmol/L, LDH – 130 U/L, complement system C3 – 1.32 g/L, С4 – 0.37 g/L, hemoglobin – 144 g/L, platelets – 302*10 9 /L; urinalysis showed: daily protein loss – 2.6 g/day, RBC – 0–1 per field. Taking into account the kidney damage, the renal fine-needle aspiration biopsy was performed, revealing histopathological findings typical of chronic thrombotic microangiopathy of extreme severity, arteriolar arteriosclerosis with total or subtotal luminal occlusion, extensive secondary perihilar segmental glomerulosclerosis (27%); and global glomerulosclerosis (55%). According to the study results, the secondary genesis of TMA was ruled out, as well as STEC-HUS and thrombotic thrombocytopenic purpura (TTP), systemic diseases (systemic lupus erythematosus, antiphospholipid syndrome (APS), scleroderma), malignancies, HIV infection, sepsis, malignant arterial hypertension, adverse drug events, or disseminated intravascular coagulation (DIC). Plasma ADAMTS-13 levels were also assessed. Its activity was 64% (normal range 93–113%) of ADAMTS-13 activity in the control plasma, thus the diagnosis of thrombocytopenic purpura was ruled out. Due to the absence of anti-CFH-antibodies the antibody origin of aHUS was also ruled out. To assess the contribution of additional factors promoting the development of TMA, the polymorphism of hemostasis genes was studied to reveal homozygous genotypes of platelet collagen receptors (ITGA2: 807 С/Е), heterozygous genotypes of fibrinogen genes (FGB: 455 G/А), folate cycle enzymes (methylenetetrahydrofolate reductase (MTHFR: 677 C/T), methionine synthase (MTR: 2756 A/G (D919G)), responsible for a pronounced tendency towards hyperhomocysteinemia. In the clinical case the diagnosis of aHUS was obvious, which was supported by the classical symptom cluster of TMA and histopathological verification in the absence of data suggestive of other pathological conditions. The peculiarity of this clinical case is the late diagnosis, long-standing course, and severity (complications such as an acute cerebrovascular accident in the vertebrobasilar area, target lesions, kidneys in particular). Results: Taking into account the primary diagnosis, treatment with a standard dose of eculizumab was initiated. After three months of treatment the patient was transferred to therapy with Russian biosimilar of eculizumab. After the switch from the original drug, the therapy with eculizumab biosimilar continued to be associated with a positive trend including a gradual decline in azotemia level (blood creatinine – 115 μmol/L (GFR by EPI – 52 mL/min/1.73m 2 ), blood urea – 7.10 mmol/L), proteinuria (daily protein loss – 0.6 g/day). The comprehensive treatment including antihypertensive therapy also led to the normalisation of ABP values. No adverse events associated with the therapy were noted. Conclusion: The obtained results demonstrate high efficacy and safety of eculizumab biosimilar in the treatment of the adult patient with aHUS.